Pengaruh Model Team Games Tournament Berbantuan Media Domino Pecahan Terhadap Hasil Belajar Siswa Kelas IV Sekolah Dasar Pada Mata Pelajaran Matematika - Ardinika, Salsabila Pratama Putri; Asih, Sri Sami (Universitas Muhammadiyah Magelang, 2026)
This study aims to examine, describe, and determine the extent to which the implementation of the Team Games Tournament learning model assisted by fraction domino media influences the improvement of Mathematics learning outcomes among fourth-grade students of SDN Donorejo 1, Demak City. The research employed a quantitative approach. Data were collected through interviews, documentation, and learning achievement tests consisting of pretests and posttests. Data analysis was conducted using quantitative analysis techniques to test the research hypothesis, applying the Independent Sample T-Test and N-Gain analysis to measure the improvement in students’ learning outcomes. The results of the t-test showed that the value of tcount (3.125) > ttable (2.004), indicating a significant difference in the mean scores between the control class and the experimental class. The average posttest score of the experimental class was 80.1786, while the control class obtained an average score of 71.2069. Furthermore, the observation results of students’ learning activities revealed that the level of activeness in the experimental class was categorized as very good, with an average score of 76%, whereas the control class achieved an average of 57%, which falls into the good category. Based on the N-Gain calculation, the improvement in learning outcomes in the experimental class was higher than that of the control class, as seen from the pretest and posttest scores obtained. Therefore, the Team Games Tournament learning model assisted by fraction domino media is proven to be effective in improving Mathematics learning outcomes on fraction material for fourth-grade students of SDN Donorejo 1, Demak City.